Pengaruh Relaksasi Kebijakan Transhipment Terhadap Kegiatan Penangkapan Ikan Ilegal (IUU Fishing) - Sarah Aisha Rizal (Al-Adalah: Jurnal Hukum dan Politik Islam, 2022)
In Indonesia, transshipment is a logistical method to maintain the fish’s quality, but in reality this activity allows IUU fishing. Through the Regulation of the Minister of Maritime Affairs and Fisheries Number 57/PERMEN-KP/2014, transshipment activities were banned because losses arising from IUU fishing were partially facilitated by transshipment; fish caught are not reported and not recorded. Transshipment covers the origin of the caught fish and how the fish are caught because the transhipment is carried out in the middle of the sea with minimal supervision, far from the port, and the fish are not landed. This policy was then relaxed through the Decree of the Director General of Capture Fisheries Number 1/PERDJPT/2016, which opened up new opportunities for transhipment but under the system of Fishing in One Operational Unit. This type of research is analytical descriptive research, using literature studies. This research shows how transshipment activities have a negative impact on the state's efforts to combat IUU fishing, and this often occurs even though a single operating system was introduced.